Wastewater Treatment by Azolla: A review - Jayasundara, Prabhasha (Diyala Agricultural Sciences Journal, 2022)
Water is vital for humans and other living things, but water pollution has become a significant issue today. Various anthropogenic agricultural, industrial, and home activities produce multiple organic and inorganic substances dissolved or suspended in water. The goal of wastewater treatment is thus twofold: to reduce water pollution while also maintaining the water supply to demand. It is based on the three 3 Rs: reduce, reuse, and recycle. However, many of the methods used are ineffective or expensive. As a result, water purification is a matter of great interest. Eco-friendly approaches are essential among the new technologies and techniques tested in wastewater treatment. Aquatic macrophytes treat water by accumulating harmful metals and nutrients. Like water filters, a variety of aquatic floats can be suggested. Azolla is one among them, and it has been used for decades. Researchers have discovered that Azolla can reduce Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), nitrogen, phosphorus, and heavy metal concentrations in wastewater; therefore, it can be utilized for wastewater treatment. Azolla also produces a lot of biomasses in wastewater. The use of Azolla in reducing eutrophication in lakes and streams and other benefits is discussed in this study. According to the literature, Azolla has a high growth rate, with a doubling date of 2-4 days. Azolla's cell wall is composed of pectin, which has a high affinity for the adsorption of organic substances. Azolla serves as a "biofilter" during wastewater treatment in this way.